2013
DOI: 10.4314/jae.v17i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Economic Empowerment of Rural Women for Climate Change Mitigation and Adaptation: Implications for Policy

Abstract: There are several ways of promoting women '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…An understanding of how women are affected by climate change and their capacity to contribute to climate adaptation strategies is essential for their effective involvement in climate change responses and for harnessing their capacity for appropriate mitigative and adaptive actions (Women's Environment & Development Organization, 2007). Studies have shown various examples in different countries where women's knowledge and actions have helped to control erosion, prevent flood damage, and improve access to water (Ajani, Onwubuya, & Mgbenka, 2013;Wuyep, Dung, Buhari, Madaki, & Bitrus, 2014). Women should therefore be an important part of decision-making processes regarding land and resource management in order to allow their knowledge to benefit entire communities.…”
Section: Climate Change and Rural Lifestylementioning
confidence: 99%
“…An understanding of how women are affected by climate change and their capacity to contribute to climate adaptation strategies is essential for their effective involvement in climate change responses and for harnessing their capacity for appropriate mitigative and adaptive actions (Women's Environment & Development Organization, 2007). Studies have shown various examples in different countries where women's knowledge and actions have helped to control erosion, prevent flood damage, and improve access to water (Ajani, Onwubuya, & Mgbenka, 2013;Wuyep, Dung, Buhari, Madaki, & Bitrus, 2014). Women should therefore be an important part of decision-making processes regarding land and resource management in order to allow their knowledge to benefit entire communities.…”
Section: Climate Change and Rural Lifestylementioning
confidence: 99%
“…Empowering and valuing women in their societies increases their capacity to improve food security under climate change and make substantial contributions to their own well-being, to that of their families and of their communities (Langer et al 2015;Ajani et al 2013 andAlston 2014) (high confidence).…”
Section: Women's Empowerment: Synergies Among Adaptation Mitigation A...mentioning
confidence: 99%
“…MCSER Publishing, Rome-Italy Vol 6 No 6 S4 December 2015 252 Ajani et al, (2013), in a research pointed out that rural women's economic activities can be promoted in several ways because their potentialities as agents of change to community development through their participation in economic and income generating activities are untapped, but, their theoretical and practical knowledge to the environment and resource is not given due consideration. Bashir et al, (2014) examines the microfinance as a strategy for poverty reduction and a prime to achieve sustainable community development.…”
Section: Background Of the Studymentioning
confidence: 99%